1997
DOI: 10.1103/physrevlett.78.2831
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Insulator Transitions in the Kondo Insulator FeSi and Classic Semiconductors Are Similar

Abstract: We have observed the metal-insulator transition in the strongly correlated insulator FeSi with the chemical substitution of Al at the Si site. The magnetic susceptibility, heat capacity, and field-dependent conductivity are measured for Al concentrations ranging from 0 to 0.08. For concentrations $0.01 we find metallic properties quantitatively similar to those measured in Si:P with the exception of a greatly enhanced quasiparticle mass. Below 2 K the temperature and field-dependent conductivity can be complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 27 publications
3
60
1
Order By: Relevance
“…For example, the magnetic susceptibility, heat capacity, thermal expansion, and elastic properties all show anomalous temperature dependences between 0 K and 800 K [15][16][17] . These have been related to the very narrow gap in the electronic band structure 15,16,[18][19][20][21][22][23] . In addition, it has been shown that phonon excitations at finite temperature can close the narrow gap, accounting for some of the observed anomalous temperature dependences [24][25][26][27][28][29][30] , in particular the experimental observation of the gap closing [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the magnetic susceptibility, heat capacity, thermal expansion, and elastic properties all show anomalous temperature dependences between 0 K and 800 K [15][16][17] . These have been related to the very narrow gap in the electronic band structure 15,16,[18][19][20][21][22][23] . In addition, it has been shown that phonon excitations at finite temperature can close the narrow gap, accounting for some of the observed anomalous temperature dependences [24][25][26][27][28][29][30] , in particular the experimental observation of the gap closing [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…The Al-doped phase FeSi 1−x Al x also forms the B20 structure, for concentrations x Al 0.2. Doping with Al leads to a fast increase in electrical conductivity, and the Al-doped FeSi has been reported to be an unusual heavy-fermion metal 6,10 . It is therefore interesting to compare the effects of hole and electron doping on the phonons.…”
Section: Introductionmentioning
confidence: 99%
“…FeSi has generated great interest as a possible d−electron Kondo insulator [3][4][5][6] , as well as a possible product from the reaction between molten iron and mantle silicates at the core-mantle boundary 2,7-9 . Many physical properties of FeSi display anomalous temperature dependences, which has been related to its peculiar electronic band structure [10][11][12][13][14][15][16]18 . For example, the magnetic susceptibility, heat capacity, thermal expansion, and elastic properties all show anomalous temperature dependences between 0 K and 800 K [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that by examining the transport and magnetic behavior across the Fe 1−x,y Mn x Co y Si series, we can study the continuous evolution from a classic weak itinerant magnet, to a metallic paramagnet, to a Kondo (or strongly correlated) insulator, and finally a fully polarized itinerant magnetic metal 7,9,12 all without a change in crystal structure (see Fig. 1).…”
mentioning
confidence: 99%